A STUDY OF GUIDELINES FOR SOLVING SOCIAL PROBLEMS OF YOUTH AT RISK BEHAVIOR GROUPS IN THE AREA OF PAPHAYOM DISTRICT, PHATTHALUNG PROVINCE - Dhanabhaddo (Tipwong), Phrasamu Thanapat; (Sakorn Nunklab), Phrakhru Wutthisakorntham; Bunrit, Somboon; Nillakan, Lanjakon (Journal of MCU Nakhondhat, 2020)
The objectives of this research were as follows : 1) To study the state of social problem of youth at risk behavior group in the area of Paphayom district, Phatthalung province. 2) To study the cause of state of social problem of the youth for risk behavior group in the area of Paphayom district, Phatthalung province. 3) To find out the suggestion and guideline for resolution of social problem of the youth for risk behavior group in the area Paphayom district, Phatthalung province and 4) For finding out the model for resolution of social problem of the youth for risk behavior group in the area of Paphayom district, Phatthalung province, this is qualitative research, data collection by interview for key informants 52 persons and a focus group from scholars 11 persons they are composed of community leader group, educated personals group, youth group and the council of child and youths group in Paphayom district, the tools for this research was structured interview from, photo and sound record. The findings are as follows: 1) The state of social problem of the youth for risk behavior group in the area of Paphayom district, Phatthalung province, is the hard problem and continuously in the recent time. These are the severe problem and real happening in the specific area which are caused by drug addict problem as mostly especially in the group of students both boys and girls and in the time of high technology and easy to connect each others with out control of parents. 2) The cause of state of social problem of the youth for risk behavior group in the area of Paphayom district, Phatthalung province, caused by carelessness of family to get pressure from family i.e. family and to make bias of parents and trait of wrong idia, they have no consults and which derived from online media play, uncontrol of parents then they get the problem of unintention they have no consults and the parents could not looking after them as good